IMPACT OF PERINATAL OVERFEEDING ON BODY MASS OF FEMALE WISTAR RATS - Mariana Narciso Constancio; Scarlett R. Raposo; William N. S. Rodrigues; Maria N. C. Peres; Marcos V. Martins; Rafael P. Lopes; Kérolym L. Cruz; Paulo Cesar de Freitas Mathias; Douglas Lopes Almeida (Arquivos do Mudi, 2023)
Childhood obesity is an important independent risk factor for later metabolic diseases, such astype 2 diabetes, dyslipidemia, and arterial hypertension. However, males and femalesrespond differently to this nutritional challenge. Here, we propose an experimental study ofthe effects of early obesity, using the litter reduction model, in the body mass of female adultWistar rats. The litters were delivered on postnatal day 0 - PN0. In PN2, the offspring ofWistar rats was standardized in 9 (normal litter – NL) and 3 (reduced litter – SL) pups.Animals were weaned at PN21 and kept at 3 per cage for both groups until PN120. In PN120,the rats were weighed and euthanized, and then the tissues were collected, according to theapproval of the Ethics in Animal Use Committee n° 4831020822. Our data points to a bodyweight difference in PN21 between the groups, where the SL group was overweight comparedto the NL group (p<0.0001). In PN120, the SL group continued with a higher weight than theNL group (p <0.01). SL rats showed increased weight in periovarian, periuterine,retroperitoneal, mesenteric and brown fat (p=0.002, p<0.0001, p=0.001, p=0.002 andp=0.0001, respectively) compared to NL animals. Taken together, the present data shows thatfemales Wistar rats are vulnerable to the effects of early in life obesity on body mass, leadingto a greater predisposition to later risk factors associated with obesity.